Recognizing the Principle of Good Faith in Concluding Contracts in Iranian Law: A Critique - Seyedali Khazaei; Hannaneh Allahmoradi (مطالعات فقه و حقوق اسلامی)
The need to comply with good faith as a general binding principle that creates obligations for the parties at the stages of concluding, executing or interpreting the contract is not explicitly addressed in Iranian law. Accordingly, there has been disagreement for years regarding the status of this principle. Some jurists, citing Article 220 of the Civil Code, have considered custom to be the equivalent of good faith. Others have equated what is discussed in our regulations titled as knowledge and lack of knowledge as mala fide and bona fide, respectively. Recently, it has been put forward that it is possible to prove the need to observe good faith in application of all rights and duties in all areas including contract law by induction from the rules related to commercial competitions, insurance contracts, mistaken intercourse, referring of uninformed principal in an unauthorized transaction for damages and the correctness of the actions of the dismissed lawyer unaware of the dismissal. However, the need to observe good faith in commercial competitions is not a matter of judicial acts. Furthermore, due to having special characteristics and the need to observe maximum good faith in the insurance contract and due to the lack of common characteristics between the latter and other contracts, its special rules cannot be extended to all other contracts. In addition, the meaning of good faith in the rules governing mistaken intercourse, referring of uninformed principal in an unauthorized transaction, the rectification of official document, and the correctness of the actions of the dismissed lawyer unaware of the dismissal is its supportive aspect and is not related to the intended meaning of good faith in this subject. Therefore, the examples presented for inductive generalization are not conventional and therefore the conditions for relying on induction in this regard are not provided.